Weathering the storm: independent writing programs in the age of fiscal austerity - Matzen, Richard N., Jr., editor; Abraham, Matthew, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2019)
Assesses the socio-economic and political conditions that surrounded the rise of independent writing programs since the 2008 financial collapse. Looking at institutional conditions and challenges programs have faced in the last ten years as they struggled to stake their turf in a rapidly changing educational environment.--Provided by publisher.
Documents of dissent / John J. Ruszkiewicz -- Forging independence and innovation in the midst of financial austerity / Lois Agnew and Eileen Schell -- Forces acting on a departmental (re-merger) / David Beard and Chongwon Park -- Growing despite austerity / Mark Longaker, Davida Charney, Diane Davis, and Alice Batt -- "And so two shall become one" / Traci A. Zimmerman -- The Great Recession / Richard N. Matzen, Jr. -- Drawing new lessons from old stories / Jamie White-Farnham -- Surviving and thriving in the writing department at Loyola University Maryland / Cindy Moore and Peggy O'Neill -- Thriving through disruption / Amy Clements, Drew M. Loewe, and Mary Rist -- Context, strategy, identity / Linda Adler-Kassner and Madeleine Sorapure -- The future of independent online writing programs / Heidi Harris and George H. Jensen -- A complex ecology / Carl Whithaus and Chris Thaiss -- Becoming a social fact / Valerie Ross, Patrick Wehner, and Rodger LeGrand -- Making a place for writing studies in a crowded institutional landscape / Frank Gaughan.
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- Economic aspects -- United States; English language -- Rhetoric -- Study and teaching (Higher) -- Political aspects -- United States; Writing centers -- Economic aspects -- United States; Writing centers -- Political aspects -- United States; Education, Higher -- Economic aspects -- United States; Global Financial Crisis, 2008-2009